Bilateral breast carcinoma in visceral crisis: Carcinoma bilateral de mama en crisis visceral - Vela Ruiz, José Manuel (2021)
Bilateral breast carcinoma is rare and infrequent , it is good to define if it occurs synchronously or metachronously, to define if the lesion in the second breast  is metastasis or a primary tumor using pathological criteria, the state and clinical condition . For the prognosis and specialized treatment to follow. We present the case of a patient with ECIV breast cancer due to contralateral breast metastasis in a state of visceral crisis at debut, with pathological anatomy of grade 2 infiltrating ductal carcinoma of the breast, absent in situ component in both breast , RE (70%) , RP (80%), Cerb2 negative, Ki67 30% in the right breast and RE (100%) RP (80%) Cerb2-Ki67 20% left breast. A chest-abdomen-pelvis tomography was performed, showing pleural effusion. bilateral and large volume ascites. It was decided to start treatment with systemic chemotherapy, reaching a complete radiological and clinical response. After achieving good control of the disease, the first hormonal line will be sought.